Variasi Dosis Spray Ekstrak Etanol Solanum melongena L. dan Cananga adorata terhadap Perubahan Gejala Toksik, Fungsi Hepar, dan Hispatologi Mencit (Mus musculus) - Zainal Fikri; Yunan Jiwintarum; Maruni Wiwin Diarti; Hady Anshory Tamhid (Politeknik Kesehatan Kemenkes Mamuju, 2022)
The purpose of this study was to determine toxic symptoms (loss of reflex), enzyme activity of SGOT and SGPT, and liver histopathology of experimental mice (Mus musculus) exposed to a combination formulation of 96% ethanol extract spray of Solanum melongena L. and Cananga adorata flower oil. True experimental research design with Post Test Only Control Group Design, this study used 4 treatment groups and 1 control group, data collected in the form of toxic symptoms (loss of reflex), SGOT enzymatic activity, and liver histopathological picture of experimental mice (Mus musculus). Which was analyzed by One Way Anova and Descriptive test. The results showed that the changes in toxic physical symptoms (loss of reflexes) of experimental mice (Mus musculus) after 30 minutes of spraying were strange reactions to walking around without direction, sensitivity to touch, changes in social interaction colliding with each other, lethargy, eye opacity and excessive blinking, respiratory rate. increased, which returned to normal at 4 hours to 168 hours after spraying. The activity of the SGOT and SGPT enzymes after 168 hours of spraying showed that the higher the dosage of the formulation, the higher the activity of the SGOT and SGPT enzymes, but the increase was still within normal limits, the histopathological results of liver morphology grading at various research doses showed Normal and Mild. Conclusion: Solanum melongena L. and Cananga adorata flower oil combined did not cause pathological effects in experimental mice (Mus musculus).